Estudios interferométricos del campo magnético en regiones de formación estelar: observaciones milimétricas con CARMA - Fernandez Lopez, Manuel (2015)
Currently, the possible role of magnetic fields in star formation processes is not clear. Despite the efforts made through single-dish observations, a stronger observational effort is required in order to broaden the sample of detections and acquire more insight into the morphology of the magnetic field at high-angular resolution scales. Here we present some results obtained from CARMA 1.25 mm continuum and spectral line polarization observations. The target of these observations were two accretion disks around a Class 0 (L1527) and a T Tauri (HL Tau) protostar and the massive star-forming region W3OH. We resolved the morphology of the magnetic field in both disks and, in W3OH, we achieved the first Zeeman detection ever made with an interferometer.